Optical film, polarizer and image display device

JP2024001665A5Pending Publication Date: 2025-04-14TOPPAN TOMOEGAWA OPTICAL FILM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022100469
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-22
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing optical films face challenges in achieving low moisture permeability, surface hardness, and bending resistance, particularly when thinner base materials are used, and conventional curing methods are not suitable for high-speed production.

Method used

A curable resin composition with specific compounds (A, B, C) and a photopolymerization initiator (D) is applied to a transparent substrate, forming a cured film with a thickness of 3 to 20 μm, which includes alicyclic hydrocarbons or aromatic rings and bromine atoms to reduce moisture permeability and enhance hardness and bending resistance.

Benefits of technology

The solution results in an optical film with excellent low moisture permeability, surface hardness, and bending resistance, suitable for thinner base materials and compatible with high-speed production processes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an optical film or the like which is excellent in the low moisture permeability, and has the surface hardness, low curling property and flex resistance.SOLUTION: An optical film includes a cured film of a curable resin composition on at least one surface of a transparent base material. The curable resin composition contains: a compound (A) which has two or more reactive functional group in one molecule and has one or more alicyclic hydrocarbons or aromatic rings in one molecule; a compound (B) which has one or more reactive functional groups in one molecule and has one or more bromine atoms in one molecule; a compound (C) which has three or more reactive functional groups in one molecule; and a photoinitiator (D). The reactive functional groups of the compounds (A)-(C) are any of (meth)acryloyl groups, epoxy groups and oxetanyl groups. The content ratio of the compound (A) in the total solid of the composition is 30-60 mass%, the content ratio of the compound (B) is 30-60 mass%, and the content ratio of the compound (C) is 10-25 mass%. The thickness of the cured film is 3-20 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical film, a polarizing plate, and an image display device. [Background technology]

[0002] Moisture in the air has a large impact on the quality of image display devices. For example, if the polarizer of a polarizing plate absorbs moisture, the display including the polarizing plate will warp, causing light leakage. To address this issue, efforts are being made to use polarizing plate protective films with low moisture permeability.

[0003] For example, Patent Document 1 describes a barrier laminate having improved barrier properties, in which an organic layer formed of an organic compound having a cyclic structure and an inorganic layer of a silicon compound are laminated on a base film. Patent Document 2 describes a curable composition containing an epoxy compound having a halogen element as a sealant for an organic EL display device. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2014 / 136590 [Patent Document 1] International Publication No. 2020 / 149384 Summary of the Invention [Problem to be solved by the invention]

[0005] In order to reduce the moisture permeability of an optical film such as a polarizing plate protective film, it is difficult to sufficiently reduce the moisture permeability by simply providing an organic layer on a substrate. On the other hand, simply providing an inorganic layer on a substrate may result in insufficient adhesion to the substrate or defects such as cracks in the inorganic layer. When providing an inorganic layer, it is preferable to laminate an organic layer and an inorganic layer as described in Patent Document 1, but this leads to an increase in the number of manufacturing steps.

[0006] In Patent Document 2, the thickness of the cured sealant is set to 100 μm, and the sealant hardness is 40 g / (m 2 ·day) or less. However, in recent years, in order to make optical films thinner, the thickness of the substrate is less than 100 μm, and providing a cured film thicker than the substrate is not preferable from the viewpoint of thinning. In addition, in order to obtain a cured film with a thickness of 100 μm, for example, several thousand mJ / cm 2 However, in a roll-to-roll continuous production method of optical films at a conveying speed of several tens of meters / min, such severe curing conditions are impossible. In addition, depending on the material of the substrate, shrinkage due to heat is large, and wrinkles due to shrinkage of the substrate are generated under heating conditions of 100°C or higher. Therefore, it is not possible to apply a sealant composition for organic EL elements to optical films.

[0007] An object of the present invention is to provide an optical film having excellent low moisture permeability, surface hardness, low curling property and bending resistance, and a polarizing plate and an image display device using the same. [Means for solving the problem]

[0008] The optical film according to the present invention has a cured film of a curable resin composition on at least one surface of a transparent substrate, the curable resin composition containing a compound (A) having two or more reactive functional groups in one molecule and having one or more alicyclic hydrocarbons or aromatic rings in one molecule, a compound (B) having one or more reactive functional groups in one molecule and having one or more bromine atoms in one molecule, a compound (C) having three or more reactive functional groups in one molecule, and a photopolymerization initiator (D), the reactive functional groups of the compounds (A), (B) and (C) being any one of an ethylenically unsaturated bond group, an epoxy group and an oxetanyl group, the content of the compound (A) being 30 to 60 mass%, the content of the compound (B) being 30 to 60 mass%, and the content of the compound (C) being 10 to 25 mass%, based on the total solid content of the composition, and the thickness of the cured film being 3 to 20 μm.

[0009] A polarizing plate and an image display device according to the present invention include the above-mentioned optical film. Effect of the Invention

[0010] According to the present invention, it is possible to provide an optical film having excellent low moisture permeability, surface hardness, low curling property and bending resistance, and a polarizing plate and an image display device using the same. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of an optical film according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] FIG. 1 is a cross-sectional view showing a schematic configuration of an optical film according to an embodiment.

[0013] The optical film 1 includes a transparent substrate 2 and a cured film 3 of a curable resin composition laminated on one side of the transparent substrate 2. In this embodiment, the cured film 3 is laminated on one side of the transparent substrate 2, but the cured film 3 may be provided on both sides of the transparent substrate 2.

[0014] The transparent substrate 2 is a film that serves as the base of the optical film 1, and is made of a material that has excellent transparency to visible light. The transparent substrate 2 may be any of an acrylic substrate, a triacetyl cellulose substrate, a cycloolefin polymer substrate, a cycloolefin copolymer substrate, a polyethylene terephthalate substrate, a polycarbonate substrate, a polyimide substrate, and a polyamide substrate. In order to reduce the moisture permeability of the optical film 1, it is preferable that the moisture permeability of the transparent substrate 2 itself is also low. Therefore, when manufacturing an optical film 1 with extremely low moisture permeability, it is preferable to use, for example, an acrylic substrate, a cycloolefin substrate, or the like.

[0015] The thickness of the transparent substrate 2 is not particularly limited, and for example, a substrate having a thickness of 10 to 200 μm can be used. In order to reduce the thickness of the optical film 1, the thickness of the transparent substrate 2 is preferably 10 to 100 μm, and more preferably 20 to 60 μm.

[0016] The cured film 3 is a functional layer that imparts low moisture permeability and surface hardness to the optical film 1. The thickness of the cured film 3 is preferably 3 to 20 μm, and more preferably 5 to 15 μm. If the thickness of the cured film 3 is less than 3 μm, the surface hardness of the optical film 1 decreases and it becomes difficult to achieve low moisture permeability, which is not preferred. If the thickness of the cured film 3 exceeds 20 μm, the optical film 1 curls due to contraction during curing of the curable resin composition, which is not preferred, and this reduces the workability (handling ability) during production and processing of the optical film 1. In addition, if the thickness of the cured film 3 exceeds 20 μm, cracks are likely to occur on the surface of the cured film 3 when the optical film 1 is bent, which is not preferred.

[0017] The curable resin composition for forming the cured film 3 contains the following compounds (A) to (D). Compound (A): A compound having two or more reactive functional groups in one molecule and having one or more alicyclic hydrocarbons or aromatic rings in one molecule. Compound (B): A compound having one or more reactive functional groups and one or more bromine atoms in one molecule. Compound (C): A compound having three or more reactive functional groups in one molecule. Photopolymerization initiator (D)

[0018] The reactive functional group possessed by the above compounds (A), (B) and (C) is preferably any one of a methacryloyl group, an epoxy group and an oxetanyl group.

[0019] The compounds (A) and (B) constitute the basic skeleton of the cured film 3 and are components that impart low moisture permeability to the cured film 3.

[0020] When gas permeates (passes) through a polymer such as the cured film 3, the gas molecules pass through the free volume portion (the gap between molecules caused by the movement of the molecular chain). Therefore, it is considered that the larger the free volume of the polymer, the easier the gas permeates, and the smaller the molecular diameter of the gas, the easier it is to permeate the polymer. In the present invention, the compound (B) in the curable resin composition has a halogen atom (bromine atom) with a larger atomic radius than hydrogen. The halogen atom reduces the free volume in the molecule, and thus inhibits the permeation of water molecules through the cured film 3. This makes it possible to make the optical film 1 less moisture permeable. In addition, when the compound (A) or (B) has an aromatic ring, stacking occurs due to the interaction of the aromatic ring, which makes the molecules denser, thereby contributing to making the optical film 1 less moisture permeable.

[0021] The compound (A) has a hydrophobic functional group (alicyclic hydrocarbon or aromatic ring), and this hydrophobic functional group reduces the moisture permeability of the optical film 1. The content of the compound (A) is 30 to 60 mass % of the total solid content of the curable resin composition. If the blending ratio of the compound (A) is outside this range, it is not preferable because it is not possible to keep the blending ratios of the compounds (B) and (C) within the suitable range.

[0022] The content of compound (B) is 30-60 mass% of the total solid content of the curable resin composition. When the content of compounds (A) and (B) is both 30-60 mass% of the total solid content, the balance between the cyclic skeleton (alicyclic hydrocarbon or aromatic ring) and the halogen element having a larger atomic radius than hydrogen is good, and excellent low moisture permeability can be obtained. When the content of compound (B) is less than 30 mass% of the total solid content of the curable resin composition, it is not preferable because the low moisture permeability due to bromine atoms is difficult to be realized. In addition, since the cured product of compound (B) is softer than the cured product of compound (A), when the content of compound (B) exceeds 60 mass% of the total solid content of the curable resin composition, it is not preferable because the hardness is deteriorated. Furthermore, compound (B) also contributes to the mitigation of curling of the cured film 3.

[0023] Compound (C) is a component that mainly crosslinks compounds (A) and (B) to impart hardness to the cured film 3. In order to impart the desired hardness to the cured film 3, compound (C) is preferably a trifunctional or higher polyfunctional compound. The content of compound (C) is 10 to 25 mass% of the total solid content of the curable resin composition. If the content of compound (C) is less than 10 mass% of the total solid content of the curable resin composition, it is not preferable because it is difficult to achieve hardness. On the other hand, if the content of compound (C) exceeds 25 mass% of the total solid content of the curable resin composition, the content of compounds (A) and (B) becomes relatively small, which is not preferable because the low moisture permeability may become insufficient. Furthermore, if the content of compound (C) exceeds 25 mass % of the total solid content of the curable resin composition, the curable resin composition will shrink more strongly when cured, causing the optical film 1 to curl more significantly, reducing the handleability of the optical film 1 during production and processing, and making the cured film 3 more susceptible to cracking when the optical film 1 is bent, which is undesirable.

[0024] The photopolymerization initiator (D) is blended to polymerize and harden the compounds (A) to (C). When the reactive functional groups of the compounds (A) to (C) are (meth)acryloyl groups, a radical polymerization initiator is used as the photopolymerization initiator (D). When the reactive functional groups of the compounds (A) to (B) are epoxy groups or oxetanyl groups, a photoacid generator is used as the photopolymerization initiator.

[0025] As the above-mentioned compound (A), a compound having an alicyclic hydrocarbon or an aromatic ring and two or more (meth)acryloyl groups, or a compound having an alicyclic hydrocarbon or an aromatic ring and two or more epoxy groups or oxetanyl groups can be used.

[0026] Examples of the difunctional or higher (meth)acrylate having an alicyclic hydrocarbon include dimethylol tricyclodecane di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, dicyclopentenyl di(meth)acrylate, dicyclopentadienyl di(meth)acrylate, bornyl di(meth)acrylate, isobornyl di(meth)acrylate, tricyclodecanyl di(meth)acrylate, adamantyl di(meth)acrylate, adamantane dimethanol di(meth)acrylate, and adamantane dimethanol di(meth)acrylate. Examples of the methacrylate include diethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, norbornane dimethylol di(meth)acrylate, cyclohexane trimethanol tri(meth)acrylate, adamantyl tri(meth)acrylate, adamantane trimethanol tri(meth)acrylate, norbornane trimethylol tri(meth)acrylate, tricyclodecane trimethanol tri(meth)acrylate, and perhydro-1,4,5,8-dimethanonaphthalene-2,3,7-(oxymethyl)tri(meth)acrylate.

[0027] Examples of difunctional or higher (meth)acrylates having an aromatic ring include EO (ethylene oxide)-modified bisphenol A di(meth)acrylate, PO (propylene oxide)-modified bisphenol A di(meth)acrylate, ECH (ethylcyclohexane)-modified bisphenol A di(meth)acrylate, EO-modified bisphenol F di(meth)acrylate, ECH-modified hexahydrophthalic acid di(meth)acrylate, and ECH-modified phthalic acid di(meth)acrylate.

[0028] Examples of difunctional or higher epoxy compounds having an alicyclic hydrocarbon include hydrogenated bisphenol A diglycidyl ether, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, 4-vinylcyclohexene dioxide, and limonene dioxide.

[0029] Examples of the bifunctional or higher functional epoxy compounds having an aromatic ring include epoxy compounds having a bisphenol skeleton such as bisphenol A type or bisphenol F type, a naphthalene skeleton, a fluorene skeleton, or a biphenyl skeleton. A specific example of the bisphenol A type epoxy compound is 2,2-bis(4-glycidyloxyphenyl)propane.

[0030] Examples of difunctional or higher functional oxetane compounds having an alicyclic hydrocarbon or an aromatic ring include EO-modified hydrogenated bisphenol A bis(3-ethyl-3-oxetanylmethyl) ether, PO-modified hydrogenated bisphenol A bis(3-ethyl-3-oxetanylmethyl) ether, ethylene oxide (EO)-modified bisphenol A bis(3-ethyl-3-oxetanylmethyl) ether, and EO-modified bisphenol F(3-ethyl-3-oxetanylmethyl) ether.

[0031] As the compound (B), a compound having a bromine atom and any one of a (meth)acryloyl group, an epoxy group compound, and an oxetanyl group can be used. Examples of the compound (B) include 2,3-dibromopropyl (meth)acrylate, tribromophenyl (meth)acrylate, EO-modified tribromophenyl (meth)acrylate, EO-modified tetrabromobisphenol A di(meth)acrylate, PO-modified tribromophenyl (meth)acrylate, PO-modified tetrabromobisphenol A di(meth)acrylate, dibromophenyl glycidyl ether, dibromoneopentyl glycol diglycidyl ether, and 3-bromooxetane.

[0032] As the compound (C), a tri- or higher functional (meth)acrylate, a tri- or higher functional epoxy compound, or a tri- or higher functional oxetane compound can be used.

[0033] Examples of the trifunctional or higher (meth)acrylate include tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethylisocyanurate tri(meth)acrylate, and glycerin tri(meth)acrylate; trifunctional (meth)acrylate compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate; Examples of the polyfunctional (meth)acrylate compound include polyfunctional (meth)acrylate compounds having three or more functional groups, such as dipentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane hexa(meth)acrylate, and dipentaerythritol polyacrylate, as well as polyfunctional (meth)acrylate compounds in which a portion of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone.

[0034] Examples of the tri- or higher functional epoxy compound include novolac type epoxy compounds, diglycerol triglycidyl ether, pentaerythritol polyglycidyl ether, and 1,3,5-tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.

[0035] Examples of trifunctional or higher oxetane compounds include oxetanyl silicate, pentaerythritol tris(3-ethyl-3-oxetanylmethyl) ether, pentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl) ether, dipentaerythritol hexa(3-ethyl-3-oxetanylmethyl) ether, dipentaerythritol pentakis(3-ethyl-3-oxetanylmethyl) ether, dipentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl) ether, ditrimethylolpropane tetrakis(3-ethyl-3-oxetanylmethyl) ether, caprolactone-modified dipentaerythritol hexa(3-ethyl-3-oxetanylmethyl) ether, and caprolactone-modified dipentaerythritol pentakis(3-ethyl-3-oxetanylmethyl) ether.

[0036] As the radical polymerization initiator usable as the photopolymerization initiator (D), compounds such as acetophenone, benzophenone, thioxanthone, benzoin, and benzoin methyl ether can be suitably used. Examples of the radical polymerization initiator include 2,2-ethoxyacetophenone, 1-hydroxycyclohexylphenyl ketone, 2,2-dimethoxy-phenylacetophenone, dibenzoyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, and 2-chlorothioxanthone. The content of the radical polymerization initiator (D) is preferably 0.1 to 5 mass% of the total solid content of the curable resin composition.

[0037] As a photoacid generator that can be used as the photopolymerization initiator (D), compounds such as aromatic diazonium salts, aromatic sulfonium salts, aromatic iodonium salts, and metallocene compounds can be suitably used. Examples of photoacid generators include p-methoxybenzenediazonium hexafluorophosphate, diphenyl 4-thiophenoxyphenylsulfonium hexafluorophosphate, diphenyl 4-thiophenoxyphenylsulfonium hexafluoroantimonate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium pentafluorohydroxy ... Examples of the photoacid generator include 4,4-bis(thianthrenium-9-yl)-diphenyl ether dihexafluorophosphate, triphenylselenonium hexafluorophosphate, triphenylselenonium tetrafluoroborate, triphenylselenonium hexafluoroantimonate, dimethylphenacylsulfonium hexafluoroantimonate, diethylphenacylsulfonium hexafluoroantimonate, 4-hydroxyphenyldimethylsulfonium hexafluoroantimonate, 4-hydroxyphenylbenzylmethylsulfonium hexafluoroantimonate, α-hydroxymethylbenzoin sulfonic acid ester, N-hydroxyimide sulfonate, α-sulfonyloxyketone, and β-sulfonyloxyketone. The content of the photoacid generator is preferably 0.1 to 5.0 mass% of the total solid content of the curable resin composition.

[0038] Incidentally, for each of the above compounds (A) to (D), the exemplified compounds may be used alone or in combination of two or more kinds.

[0039] A leveling agent may be added to improve the surface properties of the coating film of the curable resin composition. The content of the leveling agent is preferably 0.05 to 5.0 mass% of the solid content of the composition for forming a hard coat layer. The compound usable as the leveling agent is not particularly limited, but for example, F565, RS-75, etc. manufactured by DIC Corporation can be used.

[0040] A solvent may be added to the curable resin composition as necessary. As the solvent, one or more of the following may be used in combination: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropyl alcohol, and isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as dimethyl carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone, dimethylformamide, and the like.

[0041] In addition, various additives such as an antistatic agent, an antifoaming agent, an antioxidant, an ultraviolet absorber, an infrared absorber, a colorant, a light stabilizer, a polymerization inhibitor, a photosensitizer, an antifouling agent, an oil repellent, a water repellent, and an agent for preventing fingerprints may be added to the curable resin composition as necessary.

[0042] The method for applying the curable resin composition is not particularly limited, and for example, the composition can be applied using a spin coater, a roll coater, a reverse roll coater, a gravure coater, a microgravure coater, a knife coater, a bar coater, a wire bar coater, a die coater, a dip coater, a spray coater, an applicator, or the like.

[0043] The optical film 1 according to this embodiment has low moisture permeability and can be used as a protective film for a polarizing plate. A polarizing plate can be produced by laminating protective films on both sides of a polarizer formed by adsorbing iodine or a dye to a polyvinyl alcohol (PVA) film and orienting it. The optical film 1 according to this embodiment may be laminated on both sides of the polarizer, or the optical film 1 according to this embodiment may be laminated on one side of the polarizer and a film different from the optical film 1 may be laminated on the other side. As a film different from the optical film 1, a single layer film made of any one of cycloolefin polymer, polyethylene terephthalate, and polymethyl methacrylate may be used.

[0044] Furthermore, a polarizing plate using the optical film 1 according to this embodiment can be used to configure an image display device in combination with an image display panel such as a liquid crystal panel or an organic EL panel. The image display device may include a touch panel. A polarizing plate using the optical film 1 according to this embodiment as a protective film has low moisture permeability and bending resistance, and therefore can be suitably used, for example, as an image display device to be provided on a curved surface inside a vehicle.

[0045] As described above, in the present embodiment, the cured film 3 is formed using a curable resin composition containing the above compounds (A), (B) and (C) in a specific ratio, so that an optical film 1 having a good balance between low moisture permeability, surface hardness, low curling property and bending resistance can be realized. EXAMPLES

[0046] Examples of the present invention will now be described in detail.

[0047] The materials used in the examples and comparative examples are as follows.

[0048] (A) A compound having two or more reactive functional groups in one molecule and one or more alicyclic hydrocarbons or aromatic rings in one molecule. (A-1): 2,2-bis(4-glycidyloxyphenyl)propane, B1796 (product name), manufactured by Tokyo Chemical Industry Co., Ltd. [ka] (A-2): 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, CELLOXIDE 2021P (product name), manufactured by Daicel Corporation [ka] (A-3): Dimethylol-tricyclodecane diacrylate, Light Acrylate DCP-A (product name), manufactured by Kyoeisha Chemical Co., Ltd. [ka] (A-4): EO modified bisphenol A diacrylate, Light Acrylate BP-4EAL (product name), manufactured by Kyoeisha Chemical Co., Ltd. [ka] (A') A compound having two or more reactive functional groups in one molecule and having no alicyclic hydrocarbons or aromatic rings Triethylene glycol diacrylate, Light Acrylate 3EG-A (product name), manufactured by Kyoeisha Chemical Co., Ltd. [ka]

[0049] (B) A compound having one or more reactive functional groups and one or more bromine atoms in one molecule. (B-1): 2,4-dibromophenyl glycidyl ether, D4885 (product name), manufactured by Tokyo Chemical Industry Co., Ltd. [ka] (B-2): Tribromophenyl acrylate, T3130 (product name), manufactured by Tokyo Chemical Industry Co., Ltd. [ka] (B-3): Dibromopropyl acrylate, A0910 (product name), manufactured by Tokyo Chemical Industry Co., Ltd. [ka] (B') A compound having one or more reactive functional groups in one molecule and no bromine atom 1H,1H,2H,2H-Nonafluorohexyl acrylate, N1107 (product name), manufactured by Tokyo Chemical Industry Co., Ltd. [ka]

[0050] (C) Compounds having three or more reactive functional groups in one molecule (C-1): Oxetanyl silicate, OXT191 (product name), manufactured by Toagosei Co., Ltd. [ka] (C-2): Pentaerythritol triacrylate, Light Acrylate PE-3A, (product name), manufactured by Kyoeisha Chemical Co., Ltd. [ka] (C') Compounds having two reactive functional groups in one molecule 3-Ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]}oxetane, OX-221 (trade name), manufactured by Toagosei Co., Ltd. [ka]

[0051] (D) Photopolymerization initiator (D-1): 1-hydroxycyclohexyl-phenyl ketone, Omnirad 184 (trade name), manufactured by IGM Resins BV (D-2): Diphenyl 4-thiophenoxyphenylsulfonium hexafluoroantimonate, CPI-101A (product name), manufactured by San-Apro Ltd.

[0052] (E) Levelling agent F565 (trade name), manufactured by DIC Corporation

[0053] A curable resin composition containing compounds (A) to (E) in the blending amounts shown in Tables 1 and 2 was prepared. The unit of the blending amount of each component shown in Tables 1 and 2 is parts by mass.

[0054] A coating solution obtained by diluting the adjusted curable resin composition with a solvent was applied to a TAC film (trade name: TJ40, manufactured by Fujifilm Corporation) with a thickness of 40 μm using a wire bar coater so that the film thickness after curing would be the values described in Tables 1 and 2. After heating in an oven at 60 °C for 1 minute to dry the coating film, in a UV curing apparatus under a nitrogen atmosphere (oxygen concentration 500 ppm or less), the integrated light quantity was 200 mJ / cm 2 and ultraviolet rays were irradiated so that the coating film was cured to obtain an optical film.

[0055] <Evaluation of optical film> [Pencil hardness] Using a pencil (uni, manufactured by Mitsubishi Pencil Co., Ltd.) and a Clemens type scratch tester (HA - 301, manufactured by Tester Sangyo Co., Ltd.), a scratch test was conducted on the surface of the hard coat layer of protective film A under the conditions of a load of 500 g and a scratching speed of 0.5 mm / sec. While changing the hardness of the pencil, five scratch tests were conducted at each hardness. When there were two or more scratches on the surface of the cured film of the curable resin composition, it was regarded as NG, and the maximum hardness that did not become NG was determined according to the following criteria. Judgments ○ and ◎ were regarded as passing. ◎: ≧3H 〇: 2H △: H ×: <H

[0056] [Flexural resistance] Samples were prepared by cutting the optical film into a size of 3 cm × 10 cm, and wound around an iron rod (mandrel) with a predetermined diameter (1φ - 8φ [mm]) so that the cured film was on the outside. The minimum diameter of the iron rod without cracks on the surface was used as the evaluation value of flexural resistance and judged according to the following criteria. Judgments ○ and ◎ were regarded as passing. ◎: 2mmφ or less 〇: 3mmφ △: 4mmφ ×: 5mmφ or more

[0057] The optical film was cut into a 100 mm square sample, which was then placed on a flat surface to measure the vertical distance (rise height) from the flat surface to the tips of the four corners in mm. The sum of the measurements for the four corners was used as the evaluation value, and the sample was judged according to the following criteria. ◎: 0~5mm 〇: Over 5mm and 20mm or less △: Over 20mm and 35mm or less ×: Over 35mm and 50mm or less

[0058] [Moisture permeability] The moisture permeability of the obtained optical film and the above transparent substrate was measured under conditions of 40°C and 90 RH% in accordance with the moisture permeability test method for moisture-proof packaging materials (cup method) specified in JIS Z 0208:1976. From the measured values ​​of the moisture permeability of the optical film and the measured values ​​of the moisture permeability of the transparent substrate, the moisture permeability of the cured film of the curable resin composition was calculated by the following formula (1) and judged according to the following criteria. The formula (1) is based on "Chemistry of Barrier Properties of Packaging Materials (Basic Packaging Studies Lecture 5), pp. 68-72, by Tsutomu Nakagawa, Japan Packaging Society". The judgements of ◯ and ◎ were deemed to be acceptable. 1 / a=1 / b+1 / c...Equation (1) Where: a: Moisture permeability of optical film, b: Moisture permeability of transparent substrate, c: Moisture permeability value of the curable resin composition layer It is. ◎: c value is 100g / (m 2 ·day) or less ○: c value is 100g / (m 2 ·day) and 175g / (m 2 ·day) or less △: c value is 175g / (m 2 ·day) and 250g / (m 2 ·day) or less ×: c value is 250g / (m2 ·day) super

[0059] Tables 1 and 2 show the compositions of the curable resin compositions in each of the examples and comparative examples, as well as the evaluation values ​​and judgment results for the above evaluation items.

[0060] [Table 1]

[0061] [Table 2]

[0062] The optical films according to Examples 1 to 7 were judged as ⊚ or ◯ in all the evaluation items of pencil hardness, bending resistance, curling and moisture permeability. Therefore, it was confirmed that an optical film excellent in low moisture permeability, surface hardness, low curling property and bending resistance can be realized by forming a cured film on a transparent substrate using a curable resin composition containing compounds (A), (B) and (C) in a specific ratio and setting the thickness of the cured film within a specific range.

[0063] In Comparative Example 1, the moisture permeability was poor because compounds (A) and (B) were not used, and the blending ratio of compound (C) was too high, so the pencil hardness was high, but the flex resistance and curling were poorly evaluated.

[0064] In Comparative Example 2, the moisture permeability was poor because compound (B) was not used. In addition, since compound (B) is a material that forms a cured product that is flexible and has little curl, not including compound (B) resulted in poor evaluations of flexibility and curl.

[0065] In Comparative Example 3, the moisture permeability was poor because no compound (A) was used, and the pencil hardness was poor because the compound (B) was used in an excessively large amount.

[0066] In Comparative Example 4, since the compound (C) was not used, the pencil hardness was poorly evaluated.

[0067] In Comparative Example 5, the moisture permeability was poor because a compound (A') having neither an alicyclic hydrocarbon nor an aromatic ring was used instead of the compound (A).

[0068] In Comparative Example 6, compound (B') not having a bromine atom was used instead of compound (B), and thus the moisture permeability was poorly evaluated.

[0069] In Comparative Example 7, compound (C') having less than 3 reactive functional groups was used instead of compound (C), and therefore the pencil hardness was poorly evaluated.

[0070] In Comparative Example 8, the blending ratio of compound (A) was too high and the blending ratio of compound (B) was too low, so that the moisture permeability was poorly evaluated.

[0071] In Comparative Example 9, the blending ratio of compound (B) was too high, so that the pencil hardness was poorly evaluated.

[0072] In Comparative Example 10, the blending ratio of compound (C) was too high, so the evaluation of bending resistance and curling was poor. In addition, when the blending ratio of compound (C) was too high, the amounts of compounds (A) and (B) that contribute to moisture permeability were relatively reduced, so the evaluation of moisture permeability was poor.

[0073] In Comparative Example 11, the blending ratio of compound (C) was too small, so that the pencil hardness was poorly evaluated.

[0074] In Comparative Example 12, the thickness of the cured film was too thin, and the evaluation of the pencil hardness and moisture permeability was poor.

[0075] In Comparative Example 13, the thickness of the cured film was too thick, and the evaluations of bending resistance and curling were poor. [Industrial Applicability]

[0076] The present invention can be used as an optical film for use in image display devices and the like, and is suitable, for example, as a protective film for a polarizing plate used in an image display device. [Explanation of symbols]

[0077] 1 Optical film 2 Transparent base material 3 Cured film

Claims

1. An optical film having a cured film of a curable resin composition on at least one surface of a transparent substrate, The curable resin composition is A compound (A) having two or more reactive functional groups in one molecule and one or more alicyclic hydrocarbons or aromatic rings in one molecule; A compound (B) having one or more reactive functional groups and one or more bromine atoms in one molecule; A compound (C) having three or more reactive functional groups in one molecule; A photopolymerization initiator (D) is contained, the reactive functional group of the compounds (A), (B) and (C) is any one of a (meth)acryloyl group, an epoxy group and an oxetanyl group; the content ratio of the compound (A) is 30 to 60 mass%, the content ratio of the compound (B) is 30 to 60 mass%, and the content ratio of the compound (C) is 10 to 25 mass%, based on the total solid content of the curable composition; The optical film, wherein the cured film has a thickness of 3 to 20 μm.

2. 2. The optical film according to claim 1, wherein the transparent substrate is any one of an acrylic substrate, a triacetyl cellulose substrate, a cycloolefin polymer substrate, a cycloolefin copolymer substrate, a polyethylene terephthalate substrate, a polycarbonate substrate, a polyimide substrate, and a polyamide substrate.

3. The optical film according to claim 1 or 2, which is a protective film for a polarizing plate.

4. A polarizing plate comprising the optical film according to claim 1 .

5. An image display device comprising the optical film according to claim 1 .